Service innovation: Building a sustainable competitive advantage in higher education - Cheng, Boon Liat *; Cham, Tat Huei; Dent, Michael M *; Lee, T. H. (Inderscience Enterprise, 2019)
The increasing pace of globalisation requires organisations to be innovative in their service provision to remain competitive in their industry. Higher education is one of the examples. Service innovation plays a critical role in helping universities to sustain their operations and gain a competitive edge. Therefore, the study examines the impact of service innovation on student satisfaction, and the extent to which this level of satisfaction can be translated to perceived institutional image and loyalty. The mediation effect of the institutional image is also addressed. Data was collected from 400 respondents and were analysed using structural equation modelling. All factors in service innovation (i.e., product, process, organisational and marketing innovations) have a significant effect on student satisfaction, which positively relates to perceived institutional image and loyalty. Institutional image also mediates the relationship between student satisfaction and loyalty. Implications of the findings and limitations of the study are then discussed.